2016
DOI: 10.1108/jstpm-03-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Digital oases and digital deserts in Sub-Saharan Africa

Abstract: Purpose – This paper aims to investigate whether Sub-Saharan African countries are catching up with the rest of the world in terms of online usage. Online service usage is an important component of the discourse of the “digital divide”, an emblematic term for the inequality of information and communication technology access. Design/methodology/approach – This paper is a quantitative analysis of internet and Facebook penetration coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…Some studies have found that the increase in GDP is linked with the increase in the use of the internet (Han et al, 2021;Leoveanu-Soare et al, 2020;Raza and Shah, 2020). The countries with higher GDP have observed a higher rate of internet penetration for their urban population as compared to their rural population (Billon et al, 2009;Coyle, 2014;Geovanny and Suarez, 2008;Wentrup et al, 2016). Therefore, to know the influence of GDP on internet penetration, e-waste and urban population, the following hypotheses were formulated:…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…Some studies have found that the increase in GDP is linked with the increase in the use of the internet (Han et al, 2021;Leoveanu-Soare et al, 2020;Raza and Shah, 2020). The countries with higher GDP have observed a higher rate of internet penetration for their urban population as compared to their rural population (Billon et al, 2009;Coyle, 2014;Geovanny and Suarez, 2008;Wentrup et al, 2016). Therefore, to know the influence of GDP on internet penetration, e-waste and urban population, the following hypotheses were formulated:…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…Observations made by the researchers of this study clearly show that some rural institutions of higher learning are on the wrong side of the digital divide. Digital divide is defined as the "gaps between individuals, households, business and geographic areas at different socioeconomic levels with regard to both to their opportunities to access information and communication technologies (ICTs) and to their use of the Internet for a wide variety of activities" (Organisation for Economic Co-operation and Development (OECD) 2001: 5; Wentrup et al 2016). Persons use ICTs at different levels due to differences in educational, geographic and income levels.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Inadequate ICT infrastructure adversely impacts teaching and learning at an institution. Internet is at the core of the sociotechnical pattern of an institution and those with little or no access to it are on the wrong side of the digital divide (Thaver 2015;Wentrup et al 2016).…”
Section: Information and Communication Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is a correlation between economic strength and Internet penetration (World Bank, ), and also specifically for the Sub‐Saharan continent (Wentrup, Nakamura, & Ström, ). This is a quite intuitive relation—the richer a country is, the more resources and economic capacity it has to invest in capital‐heavy infrastructure such as broadband networks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%